PENGARUH UKURAN TUBUH IKAN Poecilia reticulata PADA DAYA PEMANGSAANNYA TERHADAP LARVA Culex quinquifasciatus - Noer Moehammadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1999)
The research aimed to know the influence of Poecilia reticulata body size, in the feeding capacity on Culex quinquifasciatus larvae. The research was experimental method with Complete Random Design., each treatment with 5 replications. The taken body size of Poecilia reticulata were; 1,50 cm; 2.50 cm; and 3.50 cm. the size of fish's body was measured from the tip of snout up to the end of fin (cm). The feeding capacity was determined by subtracting the first amount of larvae which was given the rest of larvae after 24 hours. The result showed that the difference of size of Poecilia reticulate body was significantly different in the feeding capacity on Culex quinquefasciatus larvae. The fish whose body size was 1.50 cm had the lowest feeding capacity by eating 77.2 larvae for average, and the highest one was the fist which body size was 2.50 cm by eating 113.6 larvae for average, subsequently the feeding capacity decrease to the fish which body size was 3.50 cm because of eating 100,6 larvae for 24 hours.